Verification, model checking, and abstract interpretation : 13th International Conference, VMCAI 2012, Philadelphia, PA, USA, January 22-24, 2012. Proceedings - Rybalchenko, Andrey; Kuncak, Viktor (Lecture Notes in Computer Science,, 2012)
This book constitutes the refereed proceedings of the 13th International Conference on Verification, Model Checking, and Abstract Interpretation, VMCAI 2012, held in Philadelphia, PA, USA, in January 2012, co-located with the Symposium on Principles of Programming Languages, POPL 2012. The 26 revised full papers presented were carefully reviewed and selected from 70 submissions. The papers cover a wide range of topics including program verification, model checking, abstract interpretation, static analysis, deductive methods, program certification, debugging techniques, abstract domains, type systems, and optimization.